Possible radioprotective effect of folic acid supplementation on low dose ionizing radiation-induced genomic instability in vitro - Padula, Gisel (2016)
Ionizing radiation (IR) induces DNA damage through production of single and double-strand breaks and reactive oxygen species (ROS). Folic acid (FA) prevents radiation-induced DNA damage by modification of DNA synthesis and/or repair and as a radical scavenger. We hypothesized that in vitro supplementation with FA will decrease the sensitivity of cells to genetic damage induced by low dose of ionizing radiation. Annexin V, comet and micronucleus assays were performed in cultured CHO cells. After 7 days of pre-treatment with 0, 100, 200 or 300 nM FA, cultures were exposed to radiation (100 mSv). Two un-irradiated controls were executed (0 and 100 nM FA). Data were statistically analyzed with X2-test and linear regression analysis (P < 0.05). We observed a significantly decreased frequency of apoptotic cells with the increasing FA concentration (P < 0.05). The same trend was observed when analyzing DNA damage and chromosomal instability (P < 0.05 for 300 nM). Only micronuclei frequencies showed significant differences for linear regression analysis (R2 = 94.04; P < 0.01). Our results have demonstrated the radioprotective effect of folic acid supplementation on low dose ionizing radiation-induced genomic instability in vitro; folate status should be taken into account when studying the effect of low dose radiation in environmental or occupational exposure.